MENGURAI KONFLIK KOMUNAL INTERNAL NEGERI-NEGERI ISLAM DI JAZIRAH LEIHITU, MALUKU TENGAH - Ridwan Tunny (DIALEKTIKA, 2020)
ABSTRACT This article is part of a field study to describe and parse the root of internal communal conflicts in the Muslim community of jazirah Leihitu, Central Maluku. For decades, the conflict between Muslim countries is difficult solved completely. The study was started with a vision that emerged from the dream that the resolution of communal conflicts between Islamic countries in Maluku can happen completely and peace can be realized in a sustainable manner if the actors of conflict has always felt as a victim have been turned into survivors. In other words, the victim has to be part of the solution. The first step to realizing this vision is to unravel the roots of the conflicts that occur. The study was conducted using qualitative methods to approach the Sociology of Religion. Data retrieval research carried out from June to September 2015. The research data consists of historical data and actual conditions related to the communal conflict in the research sites. Historical data include recording the subject and the experience of events that have been published in both official documents and personal property actors in the field. Actual data includes the reality and the escalation of the conflict, the patterns and sociological-philosophical meaning will be revealed through interviews and observations participate. The study shows that various internal conflicts Muslims in the peninsula Leihitu, it can be concluded that komunall violence is something that is implicated in the domestic society of these kings. Some roots of the conflict that has been identified is kenalakan adolescents and the influence of liquor, the completion of which is not comprehensive and complete, problem history and customs, and legal settlement have not touched base value.